Associations between intolerance of uncertainty, paranoia, anxiety, and depression: Evidence from an international multisite sample - Jayne Morriss; Brandon A. Gaudiano; Suzanne H. So; Jessica Kingston; Tania Lincoln; Eric M. J. Morris; Lyn Ellett (Mental Health Science)
Abstract Intolerance of uncertainty (IU; the tendency to find uncertainty aversive) and paranoia (e.g., excessive mistrust of others), are both associated with anxiety and depression symptoms. While previous research has primarily focused on IU and paranoia separately, there is recent evidence to suggest that IU and paranoia are linked and may interact to increase risk for anxiety, depression, and schizophrenia‐spectrum conditions. The aims of the current study were to assess: (1) the extent to which IU (total score and subscales), paranoia, anxiety, and depression are associated and (2) whether the interaction between IU and paranoia is associated with greater anxiety and depression symptoms. To examine these aims, we conducted a survey in an international multisite sample (n = 2510). Questionnaires included: IU (total score and subscales), paranoia (RGPTS persecution subscale), anxiety, and depression. The findings revealed that: (1) IU was positively associated with paranoia (r = 0.43), anxiety (r = 0.48), and depression (r = 0.49), and (2) People with high scores on IU and paranoia showed higher anxiety and depression symptoms. Importantly, these effects remained when controlling for negative beliefs about the self and others and demographic factors. Additionally, the inhibitory IU subscale (uncertainty paralysis) was related to paranoia, anxiety, and depression. However, the prospective IU subscale (desire for predictability) was only related to depression, but not paranoia and anxiety. Overall, these findings reliably demonstrate that IU and paranoia are linked, and that IU and paranoia interactions may synergistically work to affect current levels of anxiety and depression symptoms.